Unemployment, imprisonment, and the stability of punishment hypothesis: Some results using cointegration and error correction models - Hale, Chris (Journal of quantitative criminology, 1989)
A version of the “stability of punishment” hypothesis is used to illustrate the concept of cointegration and its relationship to error correction models. The hypothesis is then tested and rejected using data from England and Wales. Finally, a dynamic time-series model relating imprisonment to convictions, crime, and Unemployment is developed and tested.